Atributos morfológicos y fisiológicos de genotipos de Brachiaria en un suelo con bajo fósforo disponible y alta saturación de aluminio - Mejia Kerguelen, S; Rao, Idupulapati M.; Ramírez, H.; Louw-Gaume, A; Gaume, A; Frossard, Emmanuel (2009)
Two Brachiaria genotypes (Brachiaria decumbens, considered as better adapted and Brachiaria ruziziensis, considered as less adapted) and 8 progenies from the cross of these two (H-7, H-40, H-28 and H-58 more adapted; H-190, H-94, H-82 and H-179 less adapted) were evaluated during 6 weeks to detect differences in shoot and root attributes when grown in an acid soil from Matazul, Meta, Colombia. Results indicated that better adapted genotypes to low P had more shoot biomass, this could be explained by a greater leaf area, more P uptake in the stem and greater root volume. The root attributes, root length, root dry weight and root P content contributed to greater adaptation to low P availability in acid soils. Six weeks of plant growth was not adequate time to distinguish differences in adaptation to low P among the two parents, but it was adequate time to identify superior progenies from the crosses.